An innovative solution of dsr routing mechanism based on mobile agent in manet networks - Cường, Cung Trọng; Tú, Võ Thanh; Hải, Nguyễn Thúc (Journal of Computer Science and Cybernetics, 2013)
In this article, we focus on studying basic features of Mobile Agent system to improve routing mechanism in Mobile Ad hoc Network (MANET). Based on mobile agent, the MAR-DSR model and algorithm are proposed to optimize network capacity in highly mobile environment. The best updating algorithm for routing are based on a congestion analysis unit and route anticipating capability of each network node. Simulation on software is used to assess effectiveness of algorithm compared to DSR.